PEDIATRIC ACUTE RESPIRATORY DISTRESS SYNDROME: PRACTICAL ASPECTS OF INTENSIVE THERAPY - YU.V. BYKOV; A. N. OBEDIN; V.V. FISHER; E.V. VOLKOV (Avicenna Tajik State Medical University, 2024)
A literature review on the intensive care of pediatric acute respiratory distress syndrome (pARDS) was conducted. Information was collected by searching in ScienceDirect, PubMed, and eLibrary databases. Keywords such as "acute respiratory syndrome," "children," "intensive care," and "mechanical ventilation" were used as search terms. The review included full-text publication with statistical data analysis. Publications on the treatment of ARDS in adult patients were excluded. There are currently no proven pharmacological treatments for pARDS, and there is a lack of randomized clinical trials. Treatment mainly involves respiratory support, infusion therapy, sedation, administration of glucocorticoids (GCs), and enteral nutrition. If necessary, non-invasive ventilation with positive end-expiratory pressure is performed as the initial respiratory support method. If it is ineffective and accompanied by evidence of increasing respiratory failure, tracheal intubation and artificial ventilation are utilized. No substantial evidence supports the use of GCs for this condition. Despite the high prevalence and mortality rates of pARDS, there is still a need to optimize intensive care algorithms and the quality of care for this condition based on more extensive randomized clinical trials.